Terâvîh Namazıyla İlgili Rivayetlerin Değerlendirilmesi - Cemil Cahit MOLLAİBRAHİMOĞLU (Tasavvur: Tekirdağ İlahiyat Dergisi, 2019)
Terâvîh, for the month of Ramadan after Isha is a naafil prayer. Our Holy Prophet (PBUH) this prayer tarawih prayer personally encouraged and confirmed when he sees the that makes. Tarawih prayers on yummy himself initially congregation Hz.Can help increase the burden of the Ummah of the Prophet thought of it gave way from the application. Terâvihin risâletin teşrî ' in the last year of the rumor is, Hz.It is understood that the Prophet made this prayer once. Tarawih prayer rak'at proposed different numbers on the number.This article, the Prophet and sahâbenin was no longer have appointed their traditions with mourning prayers superclass prayers with the congregation or the number of rak'ahs, individually, their health status of rumors indicating that describes him kıldıklarını and comments can the evaluation.